2022
DOI: 10.3390/app122111054
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Preliminary Testing of a Machine Learning-Based Platform for Sales Forecasting Using a Gradient Boosting Approach

Abstract: Organizations engaged in business, regardless of the industry in which they operate, must be able to extract knowledge from the data available to them. Often the volume of customer and supplier data is so large, the use of advanced data mining algorithms is required. In particular, machine learning algorithms make it possible to build predictive models in order to forecast customer demand and, consequently, optimize the management of supplies and warehouse logistics. We base our analysis on the use of the XGBo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The study also indicated that the incorporation of additional explanatory variables can minimize forecasting errors. Similarly, GBM and LightGBM were assessed for their utility in forecasting future sales and promotions, demonstrating decent accuracy [16][17][18]. XGBoost, a widely used model in demand forecasting due to its strong performance in sales forecasting for retail, was found to be a favorable choice [19].…”
Section: Introductionmentioning
confidence: 99%
“…The study also indicated that the incorporation of additional explanatory variables can minimize forecasting errors. Similarly, GBM and LightGBM were assessed for their utility in forecasting future sales and promotions, demonstrating decent accuracy [16][17][18]. XGBoost, a widely used model in demand forecasting due to its strong performance in sales forecasting for retail, was found to be a favorable choice [19].…”
Section: Introductionmentioning
confidence: 99%